Prevalence of Anemia and Associated Risk Factor Among Pregnant Women in Al Bayda City - Libya - Nissren Majed; Asma Alkaseh; Khadija Ahmed; Eman Albrrane; Aya Suliman (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Anaemia is considered a major public health problem; playing an important contributor to mortality and morbidity among pregnant women globally, especially in developing countries and is considered a major factor responsible for low birth weight. This study was conducted to determine the prevalence of anaemia among pregnant women in AL-Bayda city, Libya and to identify their associated factor. Methods. Descriptive cross-sectional study was carried out from April 2022 to August 2022. A total of 430 pregnant women were selected using a systematic random sampling technique. The participants were included only after confirmation of the pregnancy. Data for participants accepted in this study were collected using pretested interviewer administered questionnaire, which contains socio demographic characteristics, obstetric and gynecological history, the number of days of the menstrual cycle, the period between each birth, birth method, and hemoglobin level. The analysis was performed by using the Statistical Package for social sciences SPSS version 26. Results. The percent of anaemia in the total study sample is 56.5 %. Conclusion. Awareness regarding balanced diet, regular antenatal checkups, regular intake of iron and folic acid tablet is highly recommended.